Effect of Sharia Banking RGEC toward Indonesian GDP - Yulita, Nurma; Musthofa, Muhammad Wakhid (EkBis: Jurnal Ekonomi dan Bisnis, 2022)
This investigation aims to analyze the effect of sharia banking financial performance using the RGEC method (Risk Profile, Good Corporate Governance, Earnings, Capital) on the Gross Domestic Product (GDP). The independent variables in this study were measured the Capital Adequacy Ratio (CAR), Financing to Deposit Ratio (FDR), Operating Costs to Operating Income (BOPO), Good Corporate Governance (GCG), and Return On Equity (ROE), while the dependent variables measured by the percentage of Gross Domestic Product (GDP). The type of research is quantitative with six samples of Sharia banks consisting of Bank Muamalat Indonesia, BRI Syariah, BNI Syariah, Bank Mandiri Syariah, Bank Mega Syariah, and BCA Syariah with data for the quarter of 2016 to 2020. The analysis technique data were analyzed using panel regression with a fixed effect model method processed with Eviews 12 software. The results showed that the FDR, BOPO, and ROE variables had a positive influence and were significant on Indonesia's gross domestic product. Furthermore, the CAR and GCG variables cannot influence Indonesia's economic growth. Meanwhile, the results of Test F show the RGEC ratio of sharia banks had a significant influence on the Gross Domestic Product (GDP) at the same time.